PENGARUH LINGKUNGAN SEKOLAH TERHADAP MOTIVASI BELAJAR PDBK DI SDN 117 PEKANBARU - Rifly, Annisa Fadhira; Alim, Jesi Alexander; Hermita, Neni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the school environment on the learning motivation of students with special needs (PDBK) at SD Negeri 117 Pekanbaru. The study used a quantitative approach with an explanatory research type. The sample consisted of PDBK, homeroom teachers, parents, and peers selected through purposive sampling techniques. The results showed that the school environment and PDBK learning motivation were assessed as being in the good to very good category. The Spearman test showed a positive and significant correlation between the school environment and learning motivation with an r value of 0.576 and a p value of 0.012, supported by the Chi-Square test with a p value of 0.008. The results of the F test also showed a positive and significant influence of the school environment on PDBK learning motivation, each indicated by teacher data (F count 12.287 > F table 7.709; p = 0.025; coefficient of determination 75.4%), parents (F count 7.028 > F table 4.494; p = 0.017; coefficient of determination 30.5%), and peers (F count 6.181 > F table 4.196; p = 0.019; coefficient of determination 18.1%). Thus, it can be concluded that the school environment has a positive and significant influence on the learning motivation of students with special needs at SD Negeri 117 Pekanbaru.